2001
DOI: 10.1063/1.1405002
|View full text |Cite
|
Sign up to set email alerts
|

Structural effects of the thermal treatment on a GaInNAs/GaAs superlattice

Abstract: We have studied structural changes that occur during annealing of GaInNAs/GaAs multiple quantum wells grown by metalorganic vapor-phase epitaxy (MOVPE). Different thermal treatments led to an improved room-temperature photoluminescence (PL) intensity, but also to room-temperature PL peak splitting. This splitting is related to the appearance of compositional clustering as displayed by transmission electron microscopy (TEM). In addition to this, interfacial layers on each side of the wells have also been observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…The localized transitions could be contributed by several factors, such as composition fluctuation of the GaInNAs alloy, or QW-barrier interface roughness, N localization, or a combination of the above [32][33][34][35]. For the first two factors, the composition fluctuation was observed in transmission electron microscopy (TEM) as undulation pattern across the GaInNAs alloy layer [36]. It was also reported that in the GaInNAs alloy, there could be high local In or N composition as a result of clustering during growth, and hence resulted in the above localized transitions [37].…”
Section: Resultsmentioning
confidence: 98%
“…The localized transitions could be contributed by several factors, such as composition fluctuation of the GaInNAs alloy, or QW-barrier interface roughness, N localization, or a combination of the above [32][33][34][35]. For the first two factors, the composition fluctuation was observed in transmission electron microscopy (TEM) as undulation pattern across the GaInNAs alloy layer [36]. It was also reported that in the GaInNAs alloy, there could be high local In or N composition as a result of clustering during growth, and hence resulted in the above localized transitions [37].…”
Section: Resultsmentioning
confidence: 98%
“…The annealing affects the PL in two ways. One is a strong enhancement of the radiative efficiency, which is commonly observed in annealing studies [5][6][7][8][9][10][11][12][13][14][15][16]. The other is a red shift of the InGaAsN peak position from 923 nm at 370 1C to 948 nm at 530 1C.…”
Section: Resultsmentioning
confidence: 93%
“…In few cases where heating was carried out above 650 1C, the PL efficiency was reduced due to surface degradation. The improvement in PL efficiency after heat treatments is attributed to a reduction of non-radiative centers associated with the nitrogen incorporation [5,6]. Aside from improving PL efficiency, the heat treatments usually shift the emission to lower wavelengths.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, the agreement of the HF results with our DFT calculations for scattering vectors larger than 0.3 Å −1 encourages the use of the DT results for higher order reflection like the 220 and 004 reflections. [28][29][30][31] Another important aspect of the DFT result is the orientation sensitivity at small scattering vectors. In Fig.…”
Section: Masa: Orientation Dependence and Comparison With Hf Calmentioning
confidence: 99%